(untitled) ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2023)
Background: Functional foods can be defined as foods, which beneficially affect one or more target functions in the body, beyond adequate nutritional effect, in a way that is relevant to either an improved state of health and wellbeing and/or reduction in risk of disease. Objective: To assess the Knowledge, Attitude, and Practices (KAP) of consumers for functional foods. Methodology: A descriptive cross sectional design was adopted for the study which was conducted in New Delhi. Non probability sampling method was adopted for sample (n= 101) of adult consumers in age range of 20-59 were studied in two age categories, adults (20-39 years) and middle adults (40-59 years). Knowledge, Attitude and Practice questionnaire was developed with regard to awareness regarding functional food. Data was analyzed on the basis of age range of subjects by frequency, percentage, mean, standard deviation, z score and correlation. Results: The mean ± S.D. of knowledge scores for adult category was found to be 6.18 ± 2.49 and for middle age adults it was 5.53 ± 1.85. Attitude score of adults was 19.59 ± 2.56 and for middle adults it was 20.07 ± 1.91. The practice score was 3.79 ± 1.57 for adults and for middle adults it was 4.16 ± 1.13. A significant positive correlation was seen to exist between the knowledge and attitude, attitude and practice scores of both age categories, for knowledge and practice, positive correlation was found to exist for adults. Conclusion: The results verified that awareness of functional foods is associated with greater knowledge about them, more favourable attitudes towards them, along with their increased consumption.